2021
DOI: 10.3390/ijms222212394
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid in Inflammation and the Pathogenesis of Atherosclerosis

Abstract: Hyperuricemia is a common metabolic syndrome. Elevated uric acid levels are risk factors for gout, hypertension, and chronic kidney diseases. Furthermore, various epidemiological studies have also demonstrated an association between cardiovascular risks and hyperuricemia. In hyperuricemia, reactive oxygen species (ROS) are produced simultaneously with the formation of uric acid by xanthine oxidases. Intracellular uric acid has also been reported to promote the production of ROS. The ROS and the intracellular u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 120 publications
3
129
0
4
Order By: Relevance
“…XO will be converted in UA and superoxide anion, which will lead to high intracellular amounts of superoxide anions, which may induce cell envelope damage and enhanced mutagenesis. Only mammals have XO type [ 22 ]. XDH is the most common form of XOR and, by the conversion through UA, will develop a reduced form of nicotinamide adenine nucleotide (NADH).…”
Section: Uric Acid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…XO will be converted in UA and superoxide anion, which will lead to high intracellular amounts of superoxide anions, which may induce cell envelope damage and enhanced mutagenesis. Only mammals have XO type [ 22 ]. XDH is the most common form of XOR and, by the conversion through UA, will develop a reduced form of nicotinamide adenine nucleotide (NADH).…”
Section: Uric Acid Synthesismentioning
confidence: 99%
“…In conditions that cause exposure to a hypoxic environment, such as advanced cardiac failure, pulmonary disorders, sepsis, intoxications, and others, XDH will be converted into XO [ 23 ] ( Figure 1 ). XO has an important role in preventing infections by producing mitochondrial ROS although excess formation will imbalance the oxidative and anti-oxidative equilibrium and subsequently promote a pro-inflammatory status [ 22 ]. Furthermore, once UA is synthetized, it will be transported to the circulatory system and excreted through renal and gastrointestinal pathways [ 24 ].…”
Section: Uric Acid Synthesismentioning
confidence: 99%
“…Uric acid has been associated with CV diseases and with inflammation and oxidative stress. In addition, the majority of these studies showed that elevated levels of uric acid are a potential contributor risk factor in the development and progression of CKD [ 186 , 187 ].…”
Section: Improvement Of Conventional CV and Renal Risk Factors By Sgl...mentioning
confidence: 99%
“…Intracellular urate also generates ROS and activates inflammasomes and several proinflammatory signalling pathways, resulting in proatherogenic responses. 42 Therefore, it would be theoretically reasonable that chronic inflammation and atherosclerosis progression are attenuated by SU-lowering via pharmacological XO inhibition. However, the levels of hs-CRP, a representative marker indicative of inflammatory status, were unchanged by febuxostat treatment, even at high doses, despite a substantial decrease in the SU concentration.…”
Section: Discussionmentioning
confidence: 99%